Wildlife conservation through economically responsible ecotourist: the mediator roles of attitude between anticipated emotion and intention to stay in local homestays - Ibrahim, Hayati; Mariapan, Manohar; Lim, Evelyn Ai Lin; Bidin, Sheena (MDPI, 2021)
If responsible ecotourists stay in a local homestay, this will benefit local people economically and lead to improved wildlife conservation. This study aims to examine the mediator roles of attitudes between anticipated emotion and intention. It was conducted in Penang National Park, Malaysia, and a stratified sampling method was used for collecting the data. In all, 320 sets of questionnaires were analysed using the SPSS Amos 24.0 Statistical Software Package to test the Structural Equation Modelling. The findings show that economically responsible ecotourist attitudes to staying in local homestays for wildlife conservation partially mediate the relationship between anticipated emotion and intention to stay in a local homestay for wildlife conservation. This study suggests that players in the ecotourism industry should incorporate emotional elements in their marketing strategies to promote local homestays to responsible ecotourists, which would benefit local economies.